Spectroscopic, Thermal and Crystal Structure Properties of Novel (E)-2,6 Acrylate Dye - Kocaokutgen, H.; Gür, M.; Soylu, M.S.; Lönnecke, P. (Elsevier Sci Ltd, 2005)
2,6-Dimethyl-4-(4-tert-butylphenyldiazenyl)phenyl acrylate (C21H24N2O2), containing an acryloyloxy group, first 2,6-dimethyl-4-(4-tert-butylphenyldiazenyl) phenol was prepared by reacting 4-tert-butylbenzenediazonium salt with 2,6-dimethylphenol and then its acryloyloxy derivative was synthesized in a Schotten-Bauman-type reaction. The characterisation of the synthesized azo-ester dye has been described by IR, UV-vis, 1H NMR, 13C NMR spectroscopic techniques, and elemental analysis. The structure of the present compound has been determined by single-crystal X-ray diffraction. This synthesized azo-ester compound crystallizes in monoclinic system, space group P21/c with Z = 4. The thermal behaviour of the compound has been determined by means of differential thermal analysis (DTA) and thermogravimetry (TG) techniques. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Acrylate; Azo-Ester Dyes; Crystal Structure; Diazenes; Spectral and Thermal Analysis